The importance of steel chemistry and thermal history on the sensitization behavior in austenitic stainless steels: Experimental and modeling assessment. (September 2020) - Kolli, Satish; Javaheri, Vahid; Ohligschläger, Thomas; Kömi, Jukka; Porter, David
Highlights: The microstructures that were sensitized have been characterized using TEM. A model is proposed based on experimental sensitization measurements by means of DL- EPR testing and modeling. CALPHAD based Thermo-Calc was used for the thermodynamic and kinetic calculations. Sensitization and self-healing have been estimated based on chromium depletion profiles by defining Depletion Parameter. Individual effects of alloying elements carbon, chromium and nickel on the sensitization and desensitization ihas been predicted. Abstract: The sensitization of austenitic stainless steels is dependent on various factors such as chemical composition, heat treatment temperature and time. To study these effects, the degree of sensitization in five austenitic stainless steel compositions that were subjected to isothermal heat treatments in the temperature range 550–820 °C has been determined using double loop electrochemical potentiokinetic reactivation testing. The nucleation and growth of grain boundary M23 C6 carbides, that are responsible for sensitization, has been modelled with the help of the precipitation and diffusion modules in Thermo-Calc, assuming local multicomponent equilibrium, flux balance at the carbide-matrix interface, to quantitatively predict the Cr depletion. Based on the Cr depletion characteristics, a depletion parameter has been established that can predict sensitization in austenitic stainless steels and predict the effects of individual alloying elements.